2018
DOI: 10.1101/cshperspect.a031500
|View full text |Cite
|
Sign up to set email alerts
|

Ras-Specific GTPase-Activating Proteins—Structures, Mechanisms, and Interactions

Abstract: Ras-specific GTPase-activating proteins (RasGAPs) down-regulate the biological activity of Ras proteins by accelerating their intrinsic rate of GTP hydrolysis, basically by a transition state stabilizing mechanism. Oncogenic Ras is commonly not sensitive to RasGAPs caused by interference of mutants with the electronic or steric requirements of the transition state, resulting in up-regulation of activated Ras in respective cells. RasGAPs are modular proteins containing a helical catalytic RasGAP module surround… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 214 publications
3
38
0
Order By: Relevance
“…Indeed, the behavior analysis of forebrain-specific Cre-mediated Egr2 deletion mice showed improved learning and memory in specific learning and memory tasks (Poirier et al, 2007). In the same line, we also found that BDNF increased the transcription of Dusp1and Nf1; the products of these genes-a phosphatase and a Ras-GAP, respectively-are known to downregulate Erk1/2 signaling (Lawan et al, 2013;Scheffzek and Shivalingaiah, 2019). However, one of the role associated with Arc in neurons is the endocytosis of AMPA receptors that is required for synaptic depression (Barylko et al, 2018).…”
Section: Discussionsupporting
confidence: 52%
“…Indeed, the behavior analysis of forebrain-specific Cre-mediated Egr2 deletion mice showed improved learning and memory in specific learning and memory tasks (Poirier et al, 2007). In the same line, we also found that BDNF increased the transcription of Dusp1and Nf1; the products of these genes-a phosphatase and a Ras-GAP, respectively-are known to downregulate Erk1/2 signaling (Lawan et al, 2013;Scheffzek and Shivalingaiah, 2019). However, one of the role associated with Arc in neurons is the endocytosis of AMPA receptors that is required for synaptic depression (Barylko et al, 2018).…”
Section: Discussionsupporting
confidence: 52%
“…A patient mutation substitution of this arginine to a proline residue resulted in an 8000-fold decrease in Ras-GAP activity [44,46].…”
Section: The Gap-related Domain (Grd)mentioning
confidence: 99%
“…Two ligands are involved in this model. Interaction with ligand A induces conformational changes in the β-protrusion of the PH domain, which then releases the lid-helix of the Sec domain and opens the lipid-binding cage, thereby allowing binding of the second ligand B (glycerophospholipids) ( Figure 7) [46,50]. It is possible that Sec ligand B may be a protein and not only a lipid.…”
Section: The Secph Domainmentioning
confidence: 99%
“…Consequently, loss of function of RasGAPs leads to aberrant Ras activation and increases downstream oncogenic signaling. Currently, there are 14 recognized RasGAP genes in the human genome; they all contain a GAP domain, but share limited similarity outside this region [ 11 , 12 ]. A set of additional modules is common in RasGAPs, such as Ca 2+ -binding domains (C2) and phosphatidylinositol lipid-binding motifs (pleckstrin homology (PH)).…”
Section: The Brakes: Gaps As Negative Regulators Of Ras Activitymentioning
confidence: 99%
“…A set of additional modules is common in RasGAPs, such as Ca 2+ -binding domains (C2) and phosphatidylinositol lipid-binding motifs (pleckstrin homology (PH)). The protein architecture and specific domains define six RasGAP subfamilies of shared structure and function ( Figure 1 ; for a detailed description see [ 11 , 12 ]).…”
Section: The Brakes: Gaps As Negative Regulators Of Ras Activitymentioning
confidence: 99%